PENGARUH MEDIA EDITING VIDEO BERBENTUK TUTORIAL PEMBELAJARAN TERHADAP KREATIVITAS BELAJAR SISWA KELAS XI PADA MATA PELAJARAN PRAKARYA - Mar'aen Mar'aen; Mujiburrahman Mujiburrahman (UNDIKMA, 2019)
The purpose of this study was to determined The Effect of Video Editing Tutorialstowards students’ Creativity Class XI at MA Darul Qur'an Wal Hadits Sekotong Tengah inAcademic Year 2018/2019. This study used samples from class XI at MA Darul Qur'an Wal HaditsTelaga Lebur Sekotong Tengah, West Lombok. This research was quantitative research todetermined The Effect of Video Editing Tutorials towards students’ Creativity Class XI at MADarul Qur'an Wal Hadits Sekotong Tengah. The method used in this study was questionnaire asthe main method, observation and documentation as a complementary method. Data analysis usedstatistical analysis chi square formula. The analysis was results obtained value = 15,943 while thechi square db (C-1) x (R-1) = (5-1) x (2-1) = 4 with a significance level of 5% = 9,488 thus thatthe value Chi square analysis was greater than the chi square table (15,943> 9,488). This meansthat the null hypothesis was rejected and the alternative hypothesis was accepted is: there was TheEffect of Video Editing Tutorials towards students’ Creativity Class XI at MA Darul Qur'an WalHadits Sekotong Tengah in Academic Year 2018/2019. so it can be concluded that the results ofthis study was